Two new species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk, with a review of distinctive characters of the known species of the genus - Dautova, Tatiana N. (European Journal of Taxonomy, 2018)
This paper provides descriptions of Calcigorgia gorgonians collected from the Sea of Okhotsk and shores of the Kurile Islands between 3 Aug. 1984 and 20 Aug. 1987. New species described are the deep-water gorgonians Calcigorgia matua sp. nov. and C. simushiri sp. nov., belonging to the temperate fauna of the North Pacific hemisphere. Specimens belonging to all species of the genus were examined and the distinctive characters for each one are provided and summarized in a table. A modified diagnosis of the genus is proposed. The finding of a previously undescribed species emphasizes the need of further surveys, particularly in shelf and deeper waters, in order to improve our knowledge of this neglected fauna in Far East seas.